Report of a Case of Cowper’s Gland Syringocele in an Adult Male Patient - Abdulmajeed, Hatem Abdulkareem; Mahajan, Parag Suresh; Chinnakaruppan, Shanmugavel; Al Maslamani, Nasser Jassim (British Journal of Healthcare and Medical Research, 2024)
Cowper’s gland syringocele is a rare and often underdiagnosed condition characterized by cystic dilatation of the Cowper’s gland ducts, presenting with various radiological patterns. This report details a unique case of a giant Cowper’s gland syringocele in an adult male, highlighting the MRI findings and management outcomes.